Growth and survival of lactic acid bacteria during the fermentation of durian yogurt - Waritchon, N.; Kunlaporn, P. (International Journal of Agricultural Technology, 2022)
The behaviors of lactic acid bacteria, Lactobacillus bulgaricus and Streptococcus thermophillus, during the fermentation of durian yogurt was investigated. Ripened pulp of durain was found to support the growth of the both of L.bulgaricus and S. thermophillus. The pH values ranged between 4.58-4.68, TSS 24.0-26.0%, and acidity (as lactic) 0.95-1.21% in yogurt after 24 hr of fermentation. The viable populations of lactic acid bacteria increased rapidly in the fermented yogurt after 4 hr to 12 hr fermentation with numbers averaged 1.22x107 cfu/g L.bulgaricus and 1.85x107 cfu/g S. thermophillus, their population stabilized after 12 hr to 24 hr of fermentation with numbers averaged 1.80x107 cfu/g L.bulgaricus and 1.12x107 cfu/g S. thermophillus after 24 hr of fermentation. The optimum time between 10-12 hr had the optimum characteristics of yogurt with pH 4.61-4.73, TSS 26.5%, lactic acid 0.92-1.10% and lactic bacteria count of 1.20-1.50x107cfu/g.